The Effectiveness of Problem Based Learning Aided by Gamification Teaching Materials on Students' Mathematical Problem Solving Ability - Ambarwati, Riyama; Febriana, Anita; Anggoro, Bambang Sri; Putra, Rizki Wahyu Yunian (FKIP Universitas Lampung, 2022)
The low mathematical problem solving ability of junior high school students in Pringsewu, Lampung, Indonesia is because students understand the explanations given by the teacher and are less active during the learning process. The study was conducted to determine the differences in problem solving of students who follow the learning process using the PBL model using gamification teaching materials. The research uses quantitative methods with a quasi-experimental design type of research. The population used is junior high school students in Pringsewu, Lampung, Indonesia. The research sample used cluster random sampling technique. The data analysis used was one-way ANOVA analysis of variance with a significance level of 5% using SPSS which obtained a value of sig. <0.05 so H_0 is rejected, this indicates that there is an effect. After conducting a further test in the form of a Scheffe test, it can be concluded that there is an effect of the PBL learning model using gamification teaching materials on students' mathematical problem solving abilities. Keywords: problem based learning, gamification, mathematical problem solving ability. DOI: http://dx.doi.org/10.23960/jpmipa/v23i3.pp1278-1285